PUSH-PULL CONVERTER FOR MILD-HYBRID AUTOMOTIVE APPLICATIONS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
The push-pull converter is an optimal solution for low- and medium-power automotive applications, providing galvanic isolation and simple construction. This paper evaluates the efficiency of a converter designed in a push-pull configuration for the automotive domain, powered by a 24 V ± 6 V input and delivering a 48 V output. The proposed converter, used in advanced start-stop systems for mild-hybrid and full-hybrid vehicles, operates with variable switching frequencies between 70 kHz and 300 kHz and various power levels. The output voltage ripple is a critical parameter in the design and performance of DC-DC converters, as it directly influences the required output capacitance connected in parallel with the load. Existing analytical expressions for estimating the ripple, normalized to the average output voltage, have primarily been developed under the assumption of continuous conduction mode (CCM) operation. The proper functioning of the converter and the efficiency variation across different operating regimes were validated theoretically, through simulation, and experimentally. This paper proposes a new formula that uses real circuit parameters for determining the efficiency of the push-pull converter. The derived formula has been validated through both simulation and experimental results, demonstrating strong agreement between the theoretical and experimental outcomes.  Although it provides accurate results under the analyzed conditions, the proposed formula can be further improved by including additional factors specific to real operating conditions.
Keywords: Push-pull converters; Automotive; DC-DC; Ripple; Efficiency